Employees’ performance in the Sabah public service: The role of flexible work arrangements, work-life balance, and job satisfaction - Mohd Allif Anwar Abu Bakar; Norhayati Aliju; Saizal Pinjaman; Sharifah Milda Amirul; Sunita Dasman (RSIS International, 2025)
This study investigates the impact of flexible work arrangements (FWAs) and work-life balance (WLB) on employee performance (EP) within the public sector in Sabah, Malaysia, utilizing the Theory of Planned Behavior (TPB). Data were collected from 190 respondents across various ministries and agencies under the Sabah government. Using IBM SPSS, the findings revealed that both FWAs and WLB significantly enhance employee performance, with job satisfaction serving as a crucial mediating factor. The findings underscore the importance of FWAs and WLBs in improving employee performance and suggest that policymakers should priorities these initiatives. Public sector employees view FWAs and WLBs as essential to their job satisfaction, which in turn positively influences their performance. The study highlights the need for organizations to strengthen and implement such practices to foster a more engaged and productive workforce.